갓이 백색인 느타리 신품종 ‘세나’의 육성 및 특성 - 오민지; 김민식; 임지훈; 오연이 (Journal of mushrooms, 2023)
The development of automated bottle cultivation systems has facilitated the large-scale production of Pleurotus ostreatus, a commonly cultivated oyster mushroom species in South Korea. However, as the consumption of this product is decreasing and production quantities are exceeding demand, farmers are seeking various other mushroom types and cultivars. In response to this, we have developed a new oyster mushroom cultivar named 'Sena'. This high-yielding cultivar has a white pileus and excellent quality. The white oyster mushroom cultivars 'Goni' and 'Miso' were selected as parental strains from the genetic resources of the National Institute of Horticultural and Herbal Science’s Mushroom Division. By crossing their monokaryons, hybrids were developed and subjected to cultivation trials and characteristic evaluations to select the superior cultivar. The optimal temperature for 'Sena' mycelial growth is 25–30°C, with inhibition occurring at temperatures above 30°C, whereas the temperature for mushroom growth is 14–18°C. The mushrooms grow in clusters, with the white pileus having a shallow funnel shape. Optimal mycelial growth occurs in malt extract agar medium. When cultivated in 1,100 cc bottles, the 'Sena' cultivar had 35 available individuals, surpassing the number 16 available from the control cultivar 'Goni'. The yield per bottle also increased by approximately 157 g, a 24% increase over the control cultivar amount. When 300 g samples of harvested mushrooms were packed and stored at 4°C in a cold storage facility for 28 days, the weight loss rate of ‘Sena’ was approximately 4.22%, lower than that of 'Goni'. Moreover, the changes in pileus and stipe whiteness (measuring 6.99 and 8.33, respectively) were also lower than those of the control cultivar. Since the appearance of a white cap is crucial for quality assessment, the 'Sena' cultivar is superior to the 'Goni' cultivar in terms of both weight and quality after undergoing lowtemperature storage.